Analysis of Factors Influencing the Wear of the Deep Softening Organs of the Chisel-Cultivator - Olimovna, Umarova Shakhnoza (American Journal of Biodiversity, 2025)
The quality of soil tillage, energy consumption, and total tillage costs significantly depend on the design parameters and condition of the working bodies. Therefore, prominent scientists and companies are paying special attention to the improvement of working bodies.